Performance characteristics of a microchannel heat sink using TiO2/water nanofluid and different thermophysical models - Nitiapiruk, Piyanut; Mahian, Omid; Dalkilic, Ahmet Selim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this paper, the performance of a microchannel heat sink using TiO2/water nanofluid is experimentally investigated. The dimensions of the microchannel are 500 pm width, 800 pm height, and 40 mm length, where the number of flowing channels is 40.The effects of uncertainties in thermophysical properties on the Nusselt number and friction factor are investigated by using three different sets of thermophysical models, which are based on experimental and theoretical relations. It is concluded that the use of the model which is based on experimental data is very important to estimate the friction factor, while the use of different models to calculate of thermal conductivity has no considerable effect on the prediction of Nusselt number. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Microchannel; Nanofluids; Thermophysical properties; Performance characteristics; THERMAL-CONDUCTIVITY; Thermodynamics; Mechanics